2019
DOI: 10.1002/ecy.2925
|View full text |Cite
|
Sign up to set email alerts
|

Ocean warming and tropical invaders erode the performance of a key herbivore

Abstract: Citation: Yeruham, E., M. Shpigel, A. Abelson, and G. Rilov. 2020. Ocean warming and tropical invaders erode the performance of a key herbivore. Ecology 101(2):Abstract. Climate change and bioinvasions are two facets of global change that can act in tandem to impact native species and ecosystems. However, their combined effects on key species have rarely been studied. The Mediterranean Sea is a hot spot of both ocean warming and bioinvasions, where their impact can be tested together. In recent years, the popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 81 publications
1
37
0
Order By: Relevance
“…The frequency of population collapses and local extinctions has also increased especially in land-locked basins impacted by global warming. One such case is the Levantine basin in the Mediterranean Sea (Yeruham et al, 2015(Yeruham et al, , 2019Rilov, 2016;Corrales et al, 2018;Givan et al, 2018), where native biodiversity is gradually being replaced by alien species (Katsanevakis et al, 2018). Moreover, mass mortalities are increasingly occurring in association with strong and recurrent marine heat waves (Garrabou et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The frequency of population collapses and local extinctions has also increased especially in land-locked basins impacted by global warming. One such case is the Levantine basin in the Mediterranean Sea (Yeruham et al, 2015(Yeruham et al, , 2019Rilov, 2016;Corrales et al, 2018;Givan et al, 2018), where native biodiversity is gradually being replaced by alien species (Katsanevakis et al, 2018). Moreover, mass mortalities are increasingly occurring in association with strong and recurrent marine heat waves (Garrabou et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Cystoseira and Sargassum ) through overgrazing, shifting the benthic reef habitat to turf (Sala et al, ; Vergés, Tomas, et al, ; Yeruham, Shpigel, Abelson, & Rilov, ). This state is likely maintained by the incessant forcing of rabbitfish on algae and their recruits in the turf (Bennett et al, ; Vergés, Tomas, et al, ; Yeruham et al, ). Additionally, it has been shown that competition between turfs and fucales may also inhibit the growth of the latter (O’Brien & Scheibling, ).…”
Section: Introductionmentioning
confidence: 99%
“…Throughout this expansion, rabbitfish have decimated algal forests that were dominated by canopy‐forming algae (e.g. Cystoseira and Sargassum ) through overgrazing, shifting the benthic reef habitat to turf (Sala et al, ; Vergés, Tomas, et al, ; Yeruham, Shpigel, Abelson, & Rilov, ). This state is likely maintained by the incessant forcing of rabbitfish on algae and their recruits in the turf (Bennett et al, ; Vergés, Tomas, et al, ; Yeruham et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Proper understanding of the taxonomic and functional changes that these modifications are entailing requires the availability of data on preimpact conditions. Due to the speed at which such changes are occurring in the Eastern Mediterranean, a thorough basin-scale survey of native biodiversity is mandatory before it is irremediably lost (Peleg et al 2019;Yeruham et al 2019). Acknowledgements The sorting and identification of the material was conducted during a citizen science workshop funded by the Faculty of Earth Sciences, Geography and Astronomy of the University of Vienna.…”
Section: Is Biodiversity Underestimation a Broader Pattern In The Easmentioning
confidence: 99%